The influence of teachers' professional competency and working discipline on teachers’ performance at state elementary school - Selamat Biora; Yasir Arafat; Mulyadi Mulyadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aimed to know and analyze: (1) the influence of professional competence on teachers’ performance; (2) the influence of work discipline on teachers’ performance; and (3) the influence of professional competence and work discipline simultaneously on teachers’ performance. The data in this study were collected through questionnaires and analyzed by using multiple regression analysis through the t test, F test, and determination coefficient test. The population in this study were all junior high school teachers in Banyuasin I district, Banyuasin Regency, totaling 323 people. The sampling technique in this study was probability sampling using the Slovin formula to obtain 76 teachers as the research sample. The results of the study found that: (1) there was a significant influence between professional competence and teachers’ performance; (2) there was a significant influence between work discipline on teachers’ performance; (3) there was a significant influence between professional competence and work discipline simultaneously on teachers’ performance.